SPOT SEBARAN DAN PEMANFAATAN SAGU (Metroxylon sagu) DI KABUPATEN BANJAR KALIMANTAN SELATAN - Indra Saputra; Kissinger Kissinger; Daniel Itta (Jurnal Sylva Scienteae, 2022)
The distribution and utilization of sago plants need to be known in order to be more optimal in its management. The purpose of this study was to analyze the distribution of sago plants in Banjar Regency based on geographic position and habitat type and to analyze the use of sago plants by the community around the sago stand locations in Banjar Regency. The method of determining respondents usingmethod purposive sampling  of 14 respondents from 7 districts in Banjar Regency. Primary data were obtained from interviews with respondents and field observations about the distribution of sago plants based on their habitat type. The data were then analyzed by means of data tabulation and descriptive analysis. The distribution of sago plants in Banjar Regency is located in 7 (seven) sub-districts, namely Aluh-aluh, Astambul, Gambut, Martapura, Simpang Empat, Sungai Tabuk and Karang Intan sub-districts with 23 distribution spots. Habitat types are in the form of peatlands, swamps or riverbanks that are affected by tides. Sago is used by the community in Banjar district, especially on the stems and leaves. Sago stems are generally used as animal feed, the leaves are used for roof processing. The use of sago stalks to process sago flour is only done by people in the Sungai Tabuk sub-district in Banjar Regency. The management of sago production by the community is managed independently with the provision of socialization from the local government and the products are sold using online mediaPersebaran dan pemanfaatan Tumbuhan Sagu perlu untuk diketahui agar lebih optimal dalam pengelolaannya. Tujuan dari penelitian ini ialah untuk menganalisis sebaran tumbuhan sagu di Kabupaten Banjar berdasarkan posisi geografis dan tipe habitat serta menganalisis pemanfaatan tumbuhan sagu oleh masyarakat sekitar lokasi tegakan sagu di Kabupaten Banjar. Metode penentuan responden menggunakan metode Purposive Sampling sebesar 14 responden dari 7 Kecamatan di Kabupaten Banjar. Data primer diproleh dari wawancara kepada responden dan observasi lapangan tentang persebaran tanaman Sagu bedasarkan tipe habitatnya. Data kemudian dianalisis dengan cara tabulasi data dan analisis deskriptif. Persebaran tumbuhan sagu di Kabupaten Banjar terletak di 7 (tujuh) kecamatan yaitu kecamatan Aluh-aluh, Astambul, Gambut, Martapura, Simpang Empat, Sungai Tabuk dan Karang Intan dengan 23 spot sebaran. Tipe habitatnya berupa lahan gambut, rawa atau dipinggiran sungai yang terkena pasang surut. Sagu dimanfaatkan masyarakat di kabupaten Banjar terutama pada bagian batang dan daunnya. Batang sagu umumnya digunakan sebagai pakan ternak, daunnya dimanfaatkan untuk pengolahan atap. Pemanfaatan batang sagu untuk mengolah tepung sagu hanya dilakukan oleh masyarakat di kecamatan Sungai Tabuk di Kabupaten Banjar. Pengelolaan produksi sagu oleh masyarakat dikelola secara mandiri dengan bekal sosialisasi dari pemerintah setempat dan hasil produk dijual menggunakan media online